Critical Role of the Pore Domain in the Cold Response of trpm8 Channels Identified by Ortholog Functional Comparison - Ugarte-Martinez, G; Madrid-Montecinos, R; Gonzalez-Figueroa, A; Rivera-Bravo, B; Pertusa-Pastor, M (American Society for Biochemistry and Molecular Biology Inc., 2018)
In mammals, the main molecular entity involved in innocuous cold transduction isTRPM8.This polymodal ion channel is activated by cold, cooling compounds such as menthol and voltage. Despite its relevance, the molecular determinants involved in its activation by cold remain elusive. In this study we explored the use of TRPM8 orthologs with different cold responses as a strategy to identify new molecular determinants related with their thermosensitivity. We focused on mouse TRPM8 (mTRPM8) and chicken TRPM8 (cTRPM8), which present complementary thermosensitive and chemosensitive phenotypes. Although mTRPM8 displays larger responses to cold than cTRPM8 does, the avian ortholog shows a higher sensitivity to menthol compared with the mouse channel, in both HEK293 cells and primary somatosensory neurons. We took advantage of these differences to build multiple functional chimeras between these orthologs, to identify the regions that account for these discrepancies. Using a combination of calcium imaging and patch clamping, we identified a region encompassing positions 526-556 in the N terminus, whose replacement by the cTRPM8 homolog sequence potentiated its response to agonists. More importantly, we found that the characteristic cold response of these orthologs is due to nonconserved residues located within the pore loop, suggesting that TRPM8 has evolved by increasing the magnitude of its cold response through changes in this region. Our results reveal that these structural domains are critically involved in cold sensitivity and functional modulation of TRPM8, and support the idea that the pore domain is a key molecular determinant in temperature responses of this thermo-transient receptor potential (TRP) channel. © 2018 Pertusa et al.